Freire’s problem-posing model: critical pedagogy and young learners - Nelson, Nadine; Chen, Julian (Oxford University Press, 2022)
The instructional rationale behind critical pedagogy is to provide students the opportunity to voice their personal stories and opinions, and to reflect and act upon social concerns relevant to their daily lives. Students can then practice being agents of transformation in their own lives, starting in the classroom. This paper is based on the first author’s experience of experimenting with critical pedagogy when she was teaching in the UAE. It justifies the suitability of implementing Paulo Freire’s problem-posing model with younger EFL learners. Outlining the tenets of critical pedagogy developed by Freire, the authors support the practical nature of the model and its transference to a primary setting. The authors explicate Freire’s problem-posing model as five phases, providing a background and case study application for each phase. The intention is to present a practical guide for teachers wishing to implement critical approaches in the EFL classroom.